(untitled) (Medico Legal Update, 2020)
Background/Objectives: With the recent emergence of child abuse as a social issue, national responsibility, not a family problem, is being emphasized. Child abuse is taking place in a private space of family. Abuse by biological parents is occurring continuously. Method/Statistical Analysis: This study conducted a survey of 300 children’s mother with elementary school students living in area C. Recognition of child abuse by type and awareness of how to deal with child abuse were investigated. Findings: As a result, awareness of the seriousness of the occurrence of child abuse was high. However, parents’ experience of finding abused children appeared relatively low. This is a result of parents’ inability to clearly distinguish child abuse and a lack of information about it. Improvements/Applications: Therefore, it is necessary to establish clear criteria for child abuse and provide correct knowledge through regular parental education and promotion. In addition, practical measures such as legal sanctions are needed to deal with child abuse cases.